Advances in the treatment of mycoses fungoides and Sézary syndrome: a narrative update in skin-directed therapies and immune-based treatments - Stuver, Robert; Geller, Shamir (Frontiers in Immunology, 2023)
Mycoses fungoides (MF) and Sézary syndrome (SS) are cutaneous T-cell lymphomas that are often challenging to manage given the absence of reliably curative therapies, at times high symptom burden with significant detriment to quality of life, and need for ongoing treatment for disease and symptom control. Recent developments in skin-directed treatments include optimizing the use of existing topical therapies, the introduction of known dermatological agents and treatment modalities for the specific treatment of MF/SS (such as mechlorethamine gel, calcineurin inhibitor creams, and photodynamic therapy), and novel local and topical agents. For advanced disease, dedicated clinical trials have translated to exciting progress, leading to the approval of brentuximab vedotin (2017) and mogamulizumab (2018) for relapsed MF/SS. Additional studies of other active systemic agents, including various cellular therapies, represent further attempts to add to the therapeutic armamentarium in treating MF/SS. In this review, we highlight these recent advancements, ranging from optimization of skin-directed therapies to the introduction of novel systemic agents. We focus on therapies approved in the preceding five years or under investigation in advanced-phase clinical trials.